Answer:
The new function is g(x) = Ix - 5I - 7 ⇒ answer C
Step-by-step explanation:
* Lets revise the translation of a function
- If the function f(x) translated horizontally to the right
by h units, then the new function g(x) = f(x - h)
- If the function f(x) translated horizontally to the left
by h units, then the new function g(x) = f(x + h)
- If the function f(x) translated vertically up
by k units, then the new function g(x) = f(x) + k
- If the function f(x) translated vertically down
by k units, then the new function g(x) = f(x) – k
* Now lets solve the problem
∵ f(x) = IxI
∵ f(x) is shifted 5 units to the right
∵ If the function f(x) shifted to the right by h units
∴ g(x) = f(x - h)
- Change IxI to Ix - 5I ⇒ (1)
∵ f(x) is shifted 7 uints down
∵ If the function f(x) shifted down by k units
∴ g(x) = f(x) - k
- Change f(x) to f(x) - 7 ⇒ (2)
- From (1) and (2) the new function is:
g(x) = Ix - 5I - 7
* The new function is g(x) = Ix - 5I - 7